CORRELATION OF GLOMERULAR FILTRATION RATE (GFR) ESTIMATION FORMULAE WITH MEASURED GFR IN PEDIATRIC ONCOLOGY PATIENTS - Pervez, Shazia; Anjum, Misbah; Bibi, Safia; Kulsoom, Shazia; Hussain, Wajid; Naeem, Bilquis (Journal of Ayub Medical College Abbottabad, 2022)
Background: In patients with malignancy accurate assessment of renal function is important for administration of chemotherapeutic medicines. Measurement of GFR by inulin, EDTA clearance, iohexol and 24 hrs urinary creatinine clearance (Crcl) is cumbersome so creatinine based GFR formulas have been developed for assessment of kidney function and there are variety of GFR formulas available for clinical use. Objective was to determine the correlation of estimated GFR by creatinine-based estimation formulae with measured GFR by 24-hours creatinine clearance. Methods: A cross sectional study was conducted in which all patients who underwent measured GFR (mGFR) assessment at Oncology Unit of NICH between 1st January to 31st December 2019 were enrolled in the study. Estimated Glomerular filtration rate (eGFR) of all these patients was calculated by three formulae Original Schwartz (OS), Updated Schwartz (US) and simple height independent equation (SHID). Correlation was made with mGFR by Crcl taken as gold standard using Pearson’s correlation and Linear regression analysis. Bland Altman analysis was also done to see the agreement between eGFR with mGFR. Results: Total sixty (60) patients were enrolled with mean age of 8.2±3.6 years. All three eGFR formulae exhibited a statistically significant positive correlation with mGFR (p-value <0.01). Linear regression analysis also showed a statistically significant relation between mGFR and eGFRs however, the developed regression models for all three formulae showed a low R2 values. Bland-altman analysis revealed that useful level of agreement does not exist between mGFR and eGFR by OS however, SHID and US were found to be in agreement with mGFR by Crcl. Conclusion: SHID and US equations give a good estimate of GFR and may be used in children with malignancies to estimate GFR.